Cognitive versus social aspects of pragmatic meaning: on the importance of identifying the subject as an ethical agent - Rajagopalan, Kanavillil (ALFA: Revista de Linguística, 2001)
Is it possible to reconcile the cognitive and the social aspects of pragmatic meaning? Or could it be that the two are doomed forever to be locked in a perennial tug-of-war? I argue in this paper that the radical versions of both these theses are faulty for the same reason: viz, that of seeking to capture in a handful of deterministic rules everything that takes place at the pragmatic level. Furthermore, I argue that there is an urgent need to look upon the subject of language as a conscientious agent just as much as a person endowed with consciousness. In other words, the ethical question is invariably present in the confrontation between the cognitive and the social.